2009
DOI: 10.1161/circresaha.109.205310
|View full text |Cite
|
Sign up to set email alerts
|

p53 Improves Aerobic Exercise Capacity and Augments Skeletal Muscle Mitochondrial DNA Content

Abstract: Rationale: Exercise capacity is a physiological characteristic associated with protection from both cardiovascular and all-cause mortality. p53 regulates mitochondrial function and its deletion markedly diminishes exercise capacity, but the underlying genetic mechanism orchestrating this is unclear. Understanding the biology of how p53 improves exercise capacity may provide useful insights for improving both cardiovascular as well as general health. Objective: The purpose of this study was to understand the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(217 citation statements)
references
References 39 publications
(43 reference statements)
10
203
3
1
Order By: Relevance
“…The enhanced p53 response with low carbohydrate (CHO) availability was also associated with enhanced acetyl CoA carboxylase (ACC) phosphorylation on serine 79 immediately postexercise (but not p38MAPK phosphorylation), thus suggesting that AMPK may be the dominant upstream signalling kinase regulating contractile-induced p53 phosphorylation. Interestingly, we also observed that SCO2 mRNA levels were not affected by exercise or CHO restriction (despite enhanced p53 activation), thus extending previous data from rodent muscle [15] that p53 may not regulate the SCO2 protein in skeletal muscle. It is worth noting, however, that our chosen biopsy sampling points were limited to immediately post-exercise and 3 h postexercise and hence it is possible that more detailed timecourse studies need to be performed to detect any significant effects of exercise on SCO2 expression.…”
Section: Exercise Induces Post-translational Modification Of P53 and supporting
confidence: 82%
See 2 more Smart Citations
“…The enhanced p53 response with low carbohydrate (CHO) availability was also associated with enhanced acetyl CoA carboxylase (ACC) phosphorylation on serine 79 immediately postexercise (but not p38MAPK phosphorylation), thus suggesting that AMPK may be the dominant upstream signalling kinase regulating contractile-induced p53 phosphorylation. Interestingly, we also observed that SCO2 mRNA levels were not affected by exercise or CHO restriction (despite enhanced p53 activation), thus extending previous data from rodent muscle [15] that p53 may not regulate the SCO2 protein in skeletal muscle. It is worth noting, however, that our chosen biopsy sampling points were limited to immediately post-exercise and 3 h postexercise and hence it is possible that more detailed timecourse studies need to be performed to detect any significant effects of exercise on SCO2 expression.…”
Section: Exercise Induces Post-translational Modification Of P53 and supporting
confidence: 82%
“…In a subsequent study, Park et al [15] confirmed that loss of p53 reduces exercise capacity as they observed that maximal running time to exhaustion was reduced in p53 KO animals. During submaximal running exercise, blood lactate was also threefold higher in p53 KO mice compared with wild-type animals, thus demonstrating that energy production in vivo favours glycolytic metabolism.…”
Section: P5modulates Skeletal Muscle Mitochondrialmentioning
confidence: 81%
See 1 more Smart Citation
“…1). P53 has been reported to maintain mitochondrial biogenesis and performance in skeletal muscle (Saleem et al, 2009;Park et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The mean of the control group (HFD) was set as 1.0. The primer pair's sequences used were as follows: mitochondrial DNA (forward) 5 0 -CCGCA AGGGAAAGATGAAAGAC-3 0 and (reverse) 5 0 -TCGTTT GGTTTCGGGGTTTC-3 0 (Lagouge et al 2006); nucleic DNA (forward) 5 0 -CTTAGAGGGACAAGTGGCGTTC and (reverse) 5 0 -CGCTGAGCCAGTCAGTGTAG-3 0 (Park et al 2009). …”
Section: Mitochondrial Densitymentioning
confidence: 99%